Algún paralelo tipológico más para la 'h' vasca de origen nasal - Igartua, Iván (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 2008)
The diachronic correspondence -n- > -h- is one of the typologically most marked phonological developments of the Basque language. Nevertheless, the plausibility of such an evolution is guaranteed by a particular articulatory and acoustic connection between the features of glottality and nasality named rhinoglottophilia. Some examples of its effects in different languages were gathered in Igartua (2008). In this one new typological evidence is offered in order to confirm that the process of sound change in Basque is not so rare from a cross-linguistic perspective.